PGawean: Aplikasi Mobile Lowongan Pekerjaan Kota Tegal Berbasis Unified Modeling Language (UML) - Somantri, Oman; Wibowo, Dega Surono; Faulin, Muhammad Husni (JTET (Jurnal Teknik Elektro Terapan), 2018)
The problem experienced by every person is looking for job vacancies. Job vacancy is an information about a job that available for job seekers, especially for a person who have not been employed and/or person who are freshly looking for a job accompanied under certain conditions. One reason of difficulty of getting a job is due to a lack of information about job vacancies. To overcome the problem, there needy urgent to build a system that capable to provide information about job vacancy. The purpose of this research is to build a mobile-based application named "PGawean" which can be used to help everyone, especially those located in the city of Tegal in finding job vacancy information. Mobile-based apps named "PGawean" are built with the method Unified Modeling Language (UML) to simplify the application creation process. Because the method of Unified Modeling Language (UML) provides an easy understanding of the role of each actor and class of the system created. Based on evaluation results by applying black box method, to mobile based application that has been made, it is proven that 95% function of the application that has been made can run well. The system has been created, will be implemented to facilitate the user / job seekers get job vacancy information, especially in the area of Tegal City and its neighborhood.Keywords : job vacancies, mobile-based application, Unified Modeling Languge (UML)